Teachers' Creative Strategies in Enhancing Students' Learning Motivation in Islamic Religious Education at Vocational Schools - Ananda, Fesia; Hindun; Husarida; Yahuda, M; Thontawi, M; A. Hayudini, Magna Anissa (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study explores the role of teachers' creative strategies in enhancing students' learning motivation in Islamic Religious Education (IRE) at Vocational High School (SMK) Negeri 4 Kota Jambi, a vocational school in Indonesia. Using a qualitative descriptive research design with a case study approach, data were collected through classroom observations, semi-structured interviews with teachers and students, and document analysis. The findings indicate that creative teaching strategies, including interactive questioning, contextualization of Islamic values to students' vocational fields, and student-centered activities, positively influence students’ motivation, leading to higher levels of engagement and active participation. In contrast, traditional lecture-based instruction was found to reduce motivation and engagement. The study aligns with motivational theories such as Self-Determination Theory, Expectancy-Value Theory, and Achievement Goal Theory, emphasizing the importance of autonomy, relevance, and mastery in fostering motivation. Despite the positive impact of creative strategies, teachers faced challenges such as time constraints, curriculum demands, and a lack of resources, which limited the consistent implementation of these strategies. This study contributes to the growing body of research on creative teaching practices in vocational education and offers practical insights for improving IRE teaching strategies and motivating students in vocational school settings.